Alcohol and alcohol-related harm in China: policy changes needed - Yi-lang Tang; Xiao-jun Xiang; Xu-yi Wang; Joseph F Cubells; Thomas F Babor; Wei Hao (Bulletin of the World Health Organization, 2013)
In China, alcohol consumption is increasing faster than anywhere else in the world. A steady increase in alcohol production has also been observed in the country, together with a rise in alcohol-related harm. Despite these trends, China's policies on the sale and consumption of alcoholic beverages are weak compared with those of other countries in Asia. Weakest of all are its policies on taxation, drink driving laws, alcohol sale to minors and marketing licenses. The authors of this descriptive paper draw attention to the urgent need for public health professionals and government officials in China to prioritize population surveillance, research and interventions designed to reduce alcohol use disorders. They describe China's current alcohol policies and recent trends in alcohol-related harm and highlight the need for health officials to conduct a thorough policy review from a public health perspective, using as a model the World Health Organization's global strategy to reduce the harmful use of alcohol.